Analysis of Employee Job Satisfaction at Aesthetic Clinic PL - Winda Chandra; Jacob Donald Tan (Dinasti Publisher, 2025)
The beauty industry is currently experiencing very rapid growth, driven by various factors such as increased awareness of self-care, technologicay developments, and product innovation. This purpose of this study to determine the factors that influence of job satisfaction at the PL Esthetic Clinic in increasing employee job satisfaction. This research uses a qualitative approach with a case study approach which is a research strategy focusing on-in depth exploration of one or several case in a real-life context. Researchers conduct semi-structured interviews and also direct observation in the field. Based on the results and discussion of research related to the analysis of employee job satisfaction at the PL Aesthetic Clinic, it can be concluded that a family-oriented relationship creates a collaborative and supportive work atmosphere, which increases motivation and morale. In addition, work-life balance gives empolyees the opportunity to manage stress and fulfill responsibilies outside of work, so they full more satisfied at work. Promotion also contributes to job satisfaction, as employees feel valued and have opportunities grow and advanced within the company. Safe haven from supervisors, characterized by good communication and support, further strengthens the sense of satisfaction. Low and inadequate compensation can result in dissatisfaction among employees, especially if they feel their efforts and contributions are not finacially rewarded. In addition, transparent communication with finance can create uncertainty and mistrust among employees, which in turn can lower job satisfaction levels.